HYBRID VIGOR AND GROWTH PERFORMANCE OF HYBRID MAHSEER (Tor spp.) IN GROW-OUT - Himawan, Yogi; Imron, Imron; Arifin, Otong Zaenal; Subagja, Jojo; Supriyanto, Supriyanto; Haryadi, Joni (Agency for Marine and Fisheries Extension and Human Resources, 2025)
Mahseer (Tor spp.) is a freshwater fish commodity with a high market value. However, its slow growth to reach consumable size has resulted in inadequate production. The aim of this study is to analyze the hybrid vigor - that are heterosis, heterobeltiosis, and growth performance - of a crossbred population of Mahseer (Tor spp) resulting from interspecies breeding. Broodstock of Mahseer from three different species were prepared for reciprocal breeding, producing nine offspring populations consisting of six hybrid offspring and three purebred offspring populations. The breeding process was carried out using artificial breeding methods, employing intramuscularly injected breeding stimulant hormones. Results show that the hybrid population of Tor soro and Tor tambroides exhibits better heterosis and heterobeltiosis in final weight, specific growth rate, and survival rate. The crossbreeding of Tor soro and Tor tambroides also exhibited better growth performance compared to other crossbred population in terms of final weight growth, specific growth rate, and survival rates, which were 64.20 g, 1.42%/day, and 100% respectively.